Current status and associated factors of social avoidance in postoperative breast cancer patients: a cross-sectional study - Chen, Xian; Yang, Xueli; Zhang, Qian; Chu, Tianyu; Zhang, Jiajia; Ma, Linlin; Chen, Ling; Zhao, Jie (Frontiers in Psychiatry, 2026)
BackgroundCompared with the general population, breast cancer patients undergoing chemotherapy after surgery are more likely to suffer from multiple psychological problems. Social avoidance, as a negative psychological factor, aggravates anxiety and depression, which in turn reduces patients’ socialization ability and seriously affects their spirituality, mental health, physical health, and ability to cope with the disease. However, research on social avoidance and distress in breast cancer patients remains limited. In light of the growing public concern about these issues, this study aimed to investigate the extent of social avoidance in postoperative breast cancer patients and to explore the factors that influence social avoidance.MethodsIn this cross-sectional study, 185 breast cancer patients were recruited from the Affiliated Hospital of Jiangnan University between December 2024 and May 2025. Participants completed standardized questionnaires measuring social avoidance, self-disgust, and acceptance of disability. Statistical analyses included factor identification through univariate and multivariate models, and correlation assessments to explore relationships between the study variables.ResultsThe mean score of social avoidance and distress in 185 postoperative breast cancer patients was (10.75 ± 4.27), of which, social avoidance and social distress scores were (5.24 ± 2.39) and (5.51 ± 2.33), respectively. Educational levels, receipt of postoperative breast cancer education, enlargement of scope of values, containment of disability effect, and behavioural disgust were predictors of social avoidance (p < 0.05). Social avoidance was negatively correlated with acceptance of disability (r = -0.585, p < 0.01), and acceptance of disability was negatively correlated with self-disgust (r = -0.676, p < 0.01). Social avoidance was significantly and positively correlated with self-disgust (r = 0.550, p < 0.01).ConclusionThe study found that 55.1% of breast cancer patients exhibited intermediate levels of social avoidance. Consequently, healthcare professionals are in a position to develop targeted interventions based on these factors to guide patients to tap into positive and active psychology, improve the level of social avoidance, and ultimately improve the quality of life. This, in turn, provides a basis for better implementation of psychological interventions for social avoidance in the future.